Event narratives in 11–14 year olds with autistic spectrum disorder. Issue 5 (19th July 2013) - King, Diane; Dockrell, Julie E.; Stuart, Morag
Abstract: Background: Children with autistic spectrum disorder (ASD) are known to have difficulties in narrative language and especially with use of evaluative enrichment devices. However, little is known about their production of event narratives. Aims: To establish if children with ASD differ from typically developing peers in their production of general and specific event narratives, and, if so, how this might be affected by levels of oral language. Methods & Procedures: Performance on general and specific event narrative tasks of 27 high‐functioning children with ASD, aged 11–14 years, was compared with that of language‐ and age‐matched groups of typically developing children. Narratives were coded for structural and evaluative language measures. Outcomes & Results: The general and specific event narratives of the ASD group differed from those of both comparison groups in structural language measures. They were shorter, contained fewer different word roots and had shorter mean length of utterances. In evaluative measures they differed from those of the typically developing age match group but not the younger language match group in the number of causal statements made in both event conditions, and in mental state references and evaluative devices in the specific event narrative condition. Conclusions & Implications: Children with ASD display specific difficulties with the use of grammar and vocabulary in event narratives which cannot be explained in terms of language levels. However, the use of evaluative devices was commensurate with oral language levels. Implications for intervention are discussed.